Face morphology of brazilian and peruvian populations: analysis of proportion and linear measurement indexes - Dos Santos, Elaine Cristina Sousa; Pimentel, Diego Jesus Bradariz; De Matos, Laís Lopes Machado; Magri, Laís Valencise; Da Silva, Ana Maria Bettoni Rodrigues; Da Silva, Marco Antônio Moreira Rodrigues (Brazilian Dental Science, 2017)
Objective: To compare the proportion and linear measurement indexes between Brazilian and Peruvian population through 3D stereophotogrammetry and to stablish the face profile of these two Latin American populations. Material and Methods: 40 volunteers (Brazilian n=21– 10 males and 11 females; Peruvian n=19 – 8 males and 11 females) aged between 18 and 40 years (mean of 28.7±9.1) had landmarks marked on the face. Then, 3D images were obtained (VECTRA M3) and the indexes of proportion and linear measurement (face, nose, and lips) were calculated. The data were statistically analyzed by One-Way ANOVA (p0.05). The following linear measurements showed intergroup statistically significant differences: face width and height, nose width and height, upper facial height, mouth width, protrusion of the nose tip (p